WHAT IS PLAGIARISM AND HOW TO AVOID IT? - Sunnatillayeva Dilbar Ulugbek qizi; Ibragimova Zarifa (Лучшие интеллектуальные исследования, 2024)
Abstract: The article discusses as an extensive guide on plagiarism. Although the concept is straightforward, it's important to delve into what this unethical behavior entails and how to prevent it. Plagiarism is a widespread issue across different fields. Content creators, scriptwriters, SEO writers, and students frequently encounter this problem. Conversely, some individuals intentionally engage in plagiarism to reduce time and effort.